Learning Culture of Elementary School Students: An Ethnographic Study at MI Nurul Huda Bengkulu City - Nabilah Aisyah Fitri; Annisa Nur Hasanah; Henny Friantary; Pahrozi Ahmad; Yosi Yulizah (International Journal on Advanced Science, Education, and Religion, 2025)
Learning culture is an important factor in determining the success of the learning process in elementary schools. This study aims to describe students learning culture and analyze the factors that influence it at MI Nurul Huda, Bengkulu City. This study used a qualitative approach with an ethnographic design. Data collection techniques were carried out through participatory observation, in-depth interviews, and documentation. Data analysis was conducted using an interactive model that includes data reduction, data presentation, and conclusion drawing. The results of the study indicate that students learning culture is formed through four main themes: discipline, learning habits, social interaction, and learning motivation. Studfents learning culture has generally developed well, especially in aspects of discipline and social interaction, but is not evenly distributed in the aspect of independent learning habits. The role of teachers has proven to be a key factor in shaping a learning culture through learning strategies and classroom management, while the social and cultural environment also influences students learning habits. The findings of this study indicate that learning culture is the result of an on going interaction between internal and external factors of students. Systematic efforts are needed through culture-based learning, strengthening the role of teachers, and environmental support to improve students learning culture